Synthesis of Green Zinc Oxide-Citrus Hystrix Nanoparticles and Study of Its Antimicrobial Properties - Muhamad, Aida; Raja Zainal, Raja Nur Dalilah Batrisyia; Shariff, Nurzaty Iman; Enche Zaiton, Nurul Syazwani (Multidisciplinary Applied Research and Innovation, 2025)
Green synthesis nanoparticles using plant extract have recently become one of the most preferred methods. This is due to its environmentally friendly and economical procedure and the synthesising of more stable nanoparticles. In this study, green Zinc oxide (ZnO-CH) nanoparticles have been synthesised using Citrus Hystrix (CH) leaf extract solution. The ZnO-CH nanoparticles were prepared using the precipitation method at different concentrations of CH extract solution (1%, 4% and 8%). The CH extract solutions were added to zinc acetate and oxalic acid to study the ZnO-CH shape and particle size. The ZnO-CH were then characterised for surface morphology, functional groups, and crystalline structure using Field emission scanning electron (FESEM), Fourier Transform Infrared (FTIR), and X-ray Diffraction (XRD), respectively. The results showed that the particle size of ZnO-CH using 8% CH extract and zinc acetate with an oxalic acid solution is in the range of 30.50 nm to 74.29 nm, which is lower than ZnO-CH with 1% and 4% CH extract. The FTIR analysis of all ZnO-CH samples shows multiple peaks between 660 cm-1 to 400 cm-1, indicating ZnO’s presence—the XRD patterns of ZnO-CH synthesised show all the 2θ values corresponding to the confirmation of ZnO NPs. Antimicrobials, including antibiotics, antivirals, antifungals, antiseptics, and antiparasitics, are pharmaceutical substances that treat or prevent infections. Multidrug-resistant bacteria have emerged due to the overuse of conventional antibiotics, posing a serious danger to public health worldwide. Zinc oxide nanoparticles have exhibited remarkable antimicrobial properties, while Citrus Hystrix is known for its rich bioactive compounds with potential medicinal applications. The green zinc oxide - citrus hystrix’s antimicrobial properties were assessed using an agar well diffusion method against gram-positive and gram-negative bacteria. The Mueller Hinton Broth and Agar will be used for the media.